2021
DOI: 10.1128/msystems.01079-20
|View full text |Cite
|
Sign up to set email alerts
|

Breast Milk Virome and Bacterial Microbiome Resilience in Kenyan Women Living with HIV

Abstract: Breast milk is nutritionally and immunologically beneficial in early life but is also a potential source of infection. Little is known about breast milk microbiota of women living with HIV (WLHIV), the impact of severe immunosuppression, and the contribution to mortality of HIV-exposed infants. Here, we performed metagenomic sequencing to characterize the bacterial microbiome and DNA virome of breast milk samples at 1 month postpartum from Kenyan WLHIV who were not receiving combination antiretroviral therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 56 publications
1
19
1
Order By: Relevance
“…Previous studies have characterized the breast milk bacterial microbiome and found a core microbiome in breast milk from women across geographic regions including Kenya, Spain, and the United States, among others ( 5 7 ). Staphylococcaceae and Streptococcaceae are the most abundant and prominent bacterial families found in breast milk universally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have characterized the breast milk bacterial microbiome and found a core microbiome in breast milk from women across geographic regions including Kenya, Spain, and the United States, among others ( 5 7 ). Staphylococcaceae and Streptococcaceae are the most abundant and prominent bacterial families found in breast milk universally.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that among WLHIV who are not on ART, the core breast milk bacterial microbiome is similar to that of HIV-negative women ( 5 , 6 , 15 ), and that immunosuppression does not appear to have a substantial impact on either breast milk DNA virome or bacterial microbiome ( 5 ). However, data is lacking on the impact of ART on the breast milk bacterial microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of lifestyle, maternal diet, and environment on the composition of the HM microbiota has been suggested [ 2 , 8 ]. Recently, Maqsood et al [ 30 ] found that cytomegalovirus (found in 98% of human milk samples) dominated the HM virome of HIV-positive mothers in Kenya, with the bacteriophage families Myoviridae , Siphoviridae , and Podoviridae ; virome profiles and diversity were not substantially altered by HIV immunosuppression or associated with infant mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The exact origin of the HM virome remains unclear. The bacterial content might be generated from the maternal skin microbiota, entero-mammary pathway, commensal microbiota inhabiting human breast tissue, or the infant’s oral cavity, whereas the origin of the viral content remains unknown [ 30 ]. Regardless of the sources of the microbiome composition, infants received these microbial communities regularly during breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggest that the mother-to-infant virome transmission occurs, as BM and stool viromes from mother-infant pairs shared a significant homology of bacteriophages (135,136). Recent research on the role of immunosuppression on the bacteriome and virome of breast milk in HIV-positive women discovered that bacterial and viral communities are resilient in breast milk despite immunosuppression (137). There is a definite need for more longitudinal paired mother-infant studies designed to capture the dynamic nature of the milk and infant virome.…”
Section: Viromementioning
confidence: 99%